Emotional Factors Hampering Investment in the European OECD Countries - Adam Noga; Andrzej K. Koźmiński; Katarzyna Piotrowska; Krzysztof Zagórski (Ekonomista, 2022)
In the article, the authors try to join one of the most important economic discussions, concerning the weakening of the investment dynamics in the world and in Poland. There are two explanations for this investment weakness in the world literature: 1) increased concentration and the use of dominant market positions by profitable enterprises not forced to run a strong competitive struggle and to invest, and 2) slowing down of technical progress, which no longer creates as many investment opportunities as it was in the second half of the 20th century. Analysing the changes of the so‑called the BDI ( Balanced Development Index ), the authors identify the third cause of investment weakness, which they consider to be the strongest, which is the socio‑economic imbalance of many countries (“emotionality”).